Análisis de la región reguladora del gen psif de Arabidopsis thaliana - Méndez Bravo, Alfonso (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
Can we suppose that the same type of living filaments is and has been the cause of all organic life? (Darwin E., 1794) The question of the doctor and naturalist Erasmus Darwin would lay solid foundations in the scientific work of the following years. This question was posed in five years before "the Origin of the Species" of his grandson Charles Darwin And seventy-one years before Gregor Mendel's "Experiments in Plant Hybrids", work with which Genetics begins and which explains that through a process that involves the transmission of some kind of information from one generation to the next, All life forms precede a very similar and only one biologically valuable if these in turn are able to perpetuate themselves by the transmission of their Characters to a next generation (inheritance).

¿Podemos suponer que un mismo tipo de filamentos vivientes es y ha sido la causa de toda vida orgánica?” (Darwin E., 1794). La pregunta del médico y naturalista Erasmo Darwin sentaría bases sólidas en el quehacer científico de los años siguientes. Esta pregunta fue planteada sesenta y cinco años antes de “El Origen de las Especies” de su nieto Charles Darwin y setenta y un años antes de “Experiments on Plant Hybrids” de Gregor Mendel, trabajo con el cual se inicia la Genética y el cual explica que mediante un proceso que implica la transmisión de alguna clase de información de una generación a la siguiente, todas las formas de vida preceden de una muy similar y sólo serán biológicamente valiosas si éstas a su vez son capaces de perpetuarse mediante la transmisión de sus caracteres a una siguiente generación (herencia).
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2006-0002; Región reguladora; Gen; Auxina; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3816